Kesalahan Konsep Descriptive Geometry Mahasiswa terhadap Kemampuan Spasial dalam Pembelajaran Daring di Masa Pandemi COVID-19 - Aris Hadiyan Wijaksana; Rizky Rosjanuardi (Universitas Hamzanwadi, 2021)
Spatial ability is one of the essential abilities to be mastered by students, especially in geometry. There is not much research, especially in Indonesian, that examines students' spatial abilities and their relation to Descriptive Geometry. This study aims to analyze students' misconceptions in the Descriptive Geometry course and describe the profile of students' spatial abilities in online learning during the COVID-19 pandemic. This study's subjects from the Mathematics Education Department of Universitas Negeri Jakarta. This research is descriptive qualitative. The learning was carried out in 16 meetings with three initial meetings offline, and the next 13 meetings online. The test was given twice at the 8th and 16th meetings accompanied by interviews with students who made mistakes in taking the test. The test results showed that students who made mistakes did not have the ability to spatial perception, spatial relation, and spatial orientation. However, there was a case of students who made mistakes still having the ability to spatial perception, spatial relation, and spatial orientation. The obstacles that affect students' spatial abilities are online learning that is not supported by technical matters, namely: limited internet networks and internet quota availability.